Innovative Project-Based Learning Video Tutorial Media: Development and Its Effect on Students Collaborative Skills - Masruri, Muhammad Agil; Efendi, Agus; Sumaryati, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Mastery of the 4C skills (Critical Thinking, Communication, Collaboration, Creativity) is essential for success in 21st-century education. However, the persistent challenges in developing collaboration skills highlight a critical gap in current educational practices. This research seeks to develop a Project-Based Learning (PjBL) video tutorial and assess its impact on enhancing students' collaboration skills in high school biology education. Using a Research and Development (R&D) design based on the Alessi & Trollip model, the study involved two media experts, two content specialists, three teachers, and twenty-nine students as participants. Data were gathered through observations, interviews, and questionnaires, and analyzed using the N-Gain technique to evaluate improvements in collaboration skills, alongside descriptive percentage techniques to assess the feasibility of the video media product. The urgency of this research lies in addressing the limitations of traditional teaching methods, which often fail to foster active collaboration among students. Findings from the planning phase, including interviews with biology teachers, revealed a lack of collaborative interaction in conventional classroom settings. In response, a video tutorial was developed to enhance teamwork and collaboration during project assignments. Expert validation yielded a high feasibility score of 85.3%, and user testing showed excellent results with an average score of 83.7%. The video tutorial achieved an N-Gain value of 0.52, categorized as moderate, indicating a significant improvement in students' collaboration skills. This research is significant as it provides a practical, scalable solution to improve collaborative learning through innovative media in biology education. Further studies are recommended to expand the development of PjBL-based videos for other subjects and to investigate their long-term impact on 21st-century skills.